Application of Lotka-Volterra Model in Enterprise Competition - Ming Cao (Forest Chemicals Review)
In recent years, differential equations have been widely used in many fields, such as ecological environment, engineering, medicine, economy and finance. Considering the similarity between the relationship between enterprises and the population relationship in biology, according to the competition among enterprises, the Lotka-Volterra model in differential equations is used to introduce the promotion coefficient between two enterprises for mathematical modeling. Through dynamic analysis of the model and corresponding economic explanation, how to adjust the relationship between enterprises to achieve better development is studied.